2000
DOI: 10.1148/radiology.217.2.r00nv02385
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Tumor Microcirculation during Fractionated Radiation Therapy in Patients with Rectal Carcinoma: Preliminary Results and Implications for Therapy

Abstract: Dynamic T1 mapping provides a suitable tool for monitoring tumor microcirculation during chemoirradiation and offers the potential for individual optimization of therapeutic procedures. Furthermore, these results indicate that the PI map may serve as a prognostic factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 32 publications
2
49
0
2
Order By: Relevance
“…Large, single RT doses disrupt the endothelial lining and cause a short-term increase in endothelial permeability. Smaller or fractionated doses, however, tend to decrease vascular permeability or cause no (30). They calculated a perfusion index from the shape of the arterial and tumor tissue curves and found this value to be significantly increased up to 2 weeks after the start of chemoradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Large, single RT doses disrupt the endothelial lining and cause a short-term increase in endothelial permeability. Smaller or fractionated doses, however, tend to decrease vascular permeability or cause no (30). They calculated a perfusion index from the shape of the arterial and tumor tissue curves and found this value to be significantly increased up to 2 weeks after the start of chemoradiation.…”
Section: Discussionmentioning
confidence: 99%
“…In general, these studies have shown that there is a progressive decrease in MR parameters such as enhancement or K trans which is associated with a decrease in tumor size following chemotherapy and that an increase or no change in such parameters is seen in those patients with progressive disease (40,41). Other studies have reported similar effects following radiotherapy in rectal and cervix cancers (42)(43)(44)(45) and androgen deprivation in prostate cancer (46). The reasons for these changes in DCE-MRI with a wide variety of different anti-cancer therapies might be because a proportion of their antitumor efficacy is due to direct effects on the vasculature, or that tumor cell kill results in a subsequent change in the tumor microcirculation.…”
Section: Use Of Dce-mri As a Pharmacodynamic Endpoint For Other Anti-mentioning
confidence: 82%
“…Details of inclusion criteria and therapy protocols are described elsewhere (7). In short, to minimize factors influencing microcirculatory parameters, a homogenous patient group was examined with respect to tumor type, stage, grading, and treatment.…”
Section: Patient Studiesmentioning
confidence: 99%
“…The quantification of concentration-time curves is, thereby, based on the widely used assumption of a linear relationship between changes in longitudinal relaxation rate, R 1 ϭ 1/T 1 , and CA concentration, which has recently been demonstrated (4). The T 1 -mapping technique has already been successfully used to assess microcirculatory changes in primary rectal carcinoma during combined chemoradiation therapy (7); therapy outcome could be predicted based on pretherapy examinations (8). For these studies, a prolonged bolus injection of the CA was utilized and a simple data analysis scheme was applied using the so-called PI value, calculated as the initial slope of the tissue CA concentration-time curve divided by the maximum of the arterial CA concentration.…”
mentioning
confidence: 99%